A Narrative Study On The Construction Of Teacher Professional Identity Amongst Three Tesol Teachers: From Pre-Service To Novice Teachers - Ibrahim, Mariah (2020)
This study investigated the construction of professional identity amongst three TESOL teachers from the pre-service period while doing their practicum in Malaysia and a further six weeks in the Maldives as part of their special teacher education project. The objective of this study was to gain insights into the personal experience of the participants as they explored the local and international practicum as pre-service teachers and their journey as novice teachers. The approach used for this qualitative study is through the narrative enquiry. As such, data was collected through the narratives of the participants through their written reflections, interviews, as well as field notes of the researcher during observation both during the local and international practicum. Findings revealed that the participants faced many challenges throughout this period as they struggle to be the teacher they envisioned to be. The challenges ranged from personal issues such as the need to conform, as well as classroom management issues, such as dealing with students’ behaviour and punishment. The experience between the local and international practicum proved to be a useful exercise as it gave the participants different views of becoming teacher from the one they are familiar with in the local context. The findings of this study indicated serious implications on teacher education especially in the aspect of teacher identity construction.